Inside the crawling T cell: leukocyte function-associated antigen-1 cross-linking is associated with microtubule-directed translocation of protein kinase C isoenzymes beta(I) and delta - VOLKOV, YURI (My University, 1998)
T cells activated via integrin receptors can polarize and start crawling locomotion with repeated cycles of cytoskeletal reassembly processes, many of which depend on phosphorylation. We demonstrate that protein kinase C (PKC) activation represents an essential event in induction of active T cell motility. We find that in crawling T cells triggered via cross-linking of integrin LFA-1 two PKC isoenzymes, ?(I) and , are targeted to the cytoskeleton with specific localization corresponding to the microtubule-organizing center (MTOC) and microtubules, as detected by immunocytochemistry and immunoblotting. Clustering of LFA-1 associated with its signaling function also occurs at the membrane sites adjacent to the MTOC. We further show that cells of a PKC-?-deficient clone derived from parental PKC-?-expressing T cell line can neither crawl nor develop a polarized microtubule array upon integrin cross-linking. However, their adhesion and formation of actin-based pseudopodia remain unaffected. Our data demonstrate the critical importance of the microtubule cytoskeleton in T cell locomotion and suggest a novel microtubule-directed intracellular signaling pathway mediated by integrins and involving two distinctive PKC isoforms.
PUBLISHED
Keywords: Administrative Staff Authors